Water Level Monitoring System as a Flood Detection System Based on the Internet of Things (IoT) with Quantitative Experimental Methodology - Indriyani Talitha Putri; Karina Fitriamalia; Allwine; Wahyu Aji Pulungan (STMIK Methodist Binjai, 2026)
Floods are one of the natural disasters that frequently occur in Indonesia and can cause significant losses, both in material damage and human casualties. Recently, high rainfall intensity in Bandar Lampung City has increased the potential risk of flooding in several areas. Therefore, a water level monitoring system capable of providing rapid information is needed as part of disaster mitigation efforts. This study aims to design and simulate an Internet of Things (IoT)-based flood monitoring and early warning system using the ESP32 microcontroller and HC-SR04 Sensor ultrasonik. The system was designed and tested through simulation using the Wokwi platform and integrated with Node-RED via the MQTT protocol for data transmission and visualization on a web-based monitoring dashboard. The system performs periodic water level measurements every five minutes and displays water status based on predetermined threshold levels. Simulation results show that the system can transmit data in real time and display water level information on the monitoring dashboard. Therefore, the proposed system has the potential to be implemented as a flood monitoring and early warning solution to improve community preparedness in flood-prone areas, particularly in Bandar Lampung City.